Dinamica productivității muncii în raport cu salariul mediu - condiție obligatorie pentru îmbunătățirea nivelului de trai - Barbu, Gheorghe (Calitatea Vieții, 1992)
The economic theory and practice have shown since long ago that a prosperous economy implies the observance of a whole series of relationships, a fundamental role among them being played by the faster increase of the labour productivity per wage-earner in comparison with that of the average wage. Spotlighting he negative effects of the non-observance of this relationship upon our people's living conditions, the paper suggests some solutions in order to come back to normality.